Creating a musically expressive performance : a study of vocalists' use of emotions in performance preparation - Condon, Shawn Michael (2015)
Musicians and educators understand the importance of expressivity in vocal performance. Despite the acceptance of expressivity as a crucial element in musical performance, educators have reported addressing it only cursorily or not addressing it at all when preparing for a performance. For these reasons, this research has focused on techniques used by trained musicians when preparing a performance, to be adapted and applied for use by teachers with their large vocal ensembles. Participants in this study were enrolled in vocal / operatic performance programs at universities in the United States, Ireland, Finland, and Hong Kong. Their progress was tracked throughout the semester by three questionnaires, one at the start of the semester, after a master class performance, and after their jury performance. Responses were wholly based on self-reflection and preference of learning style. Participants reported their preferences for relying on personal experiences in developing emotionally expressive performances. Participants’ responses also showed preferences for character development, exploring personal connections, and developing appropriately expressive body language. These findings were then overlaid as pedagogical techniques for teachers using the framework of Juslin’s GERMS model. These techniques have not been designed as individual lessons. Rather, they recommend small changes in teaching style that require no additional resources. These creative pedagogical approaches can enhance the students’ musical aptitude and emotional expressivity in performance.